Penetapan Honorarium Notaris dalam Praktik Pelaksanaan Jabatan Notaris - I Ketut Adi Gunawan; I Nyoman Sumardika; Ida Ayu Putu Widiati (Warmadewa Press, 2020)
The Law on Notary Position (hereafter called UUJN) states the honorarium, but in practice, it has certain limits. The uncertainty of honoraria can lead to misunderstanding between the notary and the client. This research was conducted with the aim of revealing whether the determination of the economic value of each deed in the practice of implementing the position of a notary is in accordance with the provisions of the UUJN and whether a notary can provide legal services in connotarial matters to underprivileged people. This research was designed using juridical-empirical research methods. The results of this study indicated that the determination of the economic value of each deed in the practice of implementing the position of a notary is in accordance with the provisions of UUJN as stipulated in article 36. All public officials who have agreed on the arrangement of the honorarium state that they must have a sense of binding and the existence of coercive power which is adjusted to the provisions in UUJN. In addition, a notary can provide legal services in the field of connotarization to underprivileged people based on a notary's morality and integrity. This is supported by Article 37 of the UUJN which states that notaries are required to provide services free of charge to people who cannot afford it.